Pengaruh Budaya Organisasi, Etika Kerja, dan Kepemimpinan terhadap Kinerja Pegawai Badan Keuangan dan Aset Daerah Kabupaten Sleman - Siwi Linda Rukmana; Sri Haryani; Rasistia Wisandianing Primadineska (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2020)
This study aims to determine whether there is an influence of organizational culture, work ethics, and leadership on employee performance. Research using quantitative methods with data collection techniques using questionnaires. The sample in this study are 86 civil servants of the Regional Finance and Assets Agency (BKAD) Sleman Regency, the sampling technique method is using purposive sampling method. The data analyzed by the t-test, F-test (goodness of fit), and multiple linear regression using the SPSS 22.00 program. The results of this study shows that: (1) Organizational culture has a positive significant effect on employee performance, (2) Work ethics has a positive significant effect on employee performance, (3) Leadership has a positive significant effect on the performance of employees of the Sleman Regency Regional Financial and Asset Agency (BKAD)